Determinants of ex post household coping strategies in the face of health shocks in Burkina Faso: evidence from household surveys - Guiro Jeudi Topan; Noël Thiombiano (Cogent Economics & Finance, 2025)
Household coping strategies to address health shocks are a significant concern, given the absence or low functionality of insurance. The objective of this study is to analyze the determinants of ex post household strategies in Burkina Faso. Data from the continuous multisectoral survey conducted in 2014 by the National Institute of Statistics and Demography (INSD) were utilized, and the analysis was performed with the multinomial logit model. The estimation results show that a 1 CFA franc increase in income multiplies the likelihood of resorting to savings by 10 and the likelihood of changing consumption patterns relative to asset sales by 15. On the other hand, an increase in health expenditure reduces the likelihood of resorting to savings by 30% and consumption adjustments by 36%, indicating immediate budgetary pressure. Furthermore, an additional sick person in the household reduces the likelihood of resorting to these two strategies by approximately 13%. Finally, the near-zero odds ratio associated with insured households suggests an almost systematic rejection of resorting to help from relatives as a primary strategy. The results imply that it is important that the government continues the process of implementing universal health insurance to protect households against the financial consequences of illness.